Language Use in Contemporary Igbo Music (Zien Journal of Social Sciences and Humanities, 2024)
Music is integral to the Nigerian cultural experience. Every culture has its unique musical sound used as important tool for communication. Contemporary Igbo musicians have also utilised the current state of the language, being influenced by multilingualism to facilitate communicative efficacy. This has created immense linguistic implications and greatly helped in unravelling the rich cultural heritage of the Igbo. These implications have not been critically examined. This study therefore sets to evaluate the language use in contemporary Igbo Music. The study adopted the socio-linguistic functional stylistic theory of stylistic criticism as propounded by Emmanuel Ngara and a descriptive survey research design as tools for its analysis. The study identifies figurative devices such as metaphor, simile, paradox, hyperbole, personification, Euphemism and metonymy in the study. The study finds out, among other things, that culture-based contemporary music contributes immensely to the presentation of the cultural heritage of the society in question as the contemporariness facilitates its choice by the younger generation. The study suggests that further researches should be embarked upon by linguists from other cultures in our indegeneous languages to enable the younger generations who have music as one of their best hobbies use the lyrics of these songs as an opportunity of learning not only the socio-cultural and economic way of life but also the dos and don’t of their culture